The Effect of Lecturer Service Quality and Lecture Facilities on Student Satisfaction of the Faculty of Economics and Business, Islamic University of Malang - Hanafi, Roy (Budapest International Research and Critics University, 2022)
This study aims to investigate the effect of service quality of lecturers and lecture facilities on student satisfaction. Primary data in this study was used by distributing questionnaires. The population is students of the Faculty of Economics and Business UNISMA, while the sample used is the Management, Accounting and Sharia Banking Study Program for the 2016-2018 academic year at the Faculty of Economics and Business, Islamic University of Malang. The research sample was taken using a purposive sampling method. The results of this study show that the service quality of lecturers partially affects student satisfaction and lecture facilities affect student satisfaction. Meanwhile, simultaneously the quality of lecturer services and lecture facilities affect student satisfaction.